Rekonstruksi Sistem Penilaian Pendidikan Islam Berbasis Hadis: Analisis Model Penilaian (Niat, Akhlak, Kinerja, Sosial-Emosional, Iman-Islam-Ihsan): A Reconstructing a Hadith-Based Assessment System in Islamic Education: An Analysis of Assessment Models (Intention, Morality, Performance, Social-Emotional, and Faith–Islam–Ihsan) - Nur Ainun Fadilah; Mulyawan Safwandy Nugraha (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2026)
This study aims to develop an assessment model in Islamic education through an analysis of five authentic hadiths related to intention, morality, worship, and social behavior. The hadiths were selected based on criteria of authenticity, relevance to educational evaluation, frequency of citation in educational literature, and a rigorous screening process. Employing a qualitative library research design, the study applies content and thematic analysis to primary data from classical hadith sources and secondary data from contemporary academic literature. The findings indicate that the selected hadiths can be reconstructed into five assessment models: intention-based assessment focusing on worship-oriented motivation; moral-spiritual assessment evaluating character; performance assessment emphasizing procedural accuracy; social-emotional assessment measuring empathy and cooperation; and an integrative model of faith, Islam, and ihsan that combines cognitive, affective, psychomotor, and spiritual domains. Each model is mapped into domains, indicators, and examples of preliminary assessment instruments. This study contributes a prophetic-based assessment framework that extends contemporary Islamic education assessment models by integrating spiritual intention (niyyah) and ihsan as evaluative dimensions. The results demonstrate that hadith provides a holistic and contextually relevant foundation for developing assessment systems in Islamic education.